Minimum Inhibitory Concentration of Chitosan and Coconut Shell Liquid Smoke Against Staphylococcus aureus and Escherichia coli - Artika, Odilia Emeralda Dian; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aimed to determine the minimum inhibitory concentration (MIC) of chitosan and coconut shell liquid smoke against S. aureus and E. coli cultures. The treatments consisted of varying concentrations of Chitosan (0%, 1%, 1.5%, 2%, and 2.5%) and liquid smoke (0%, 1%, 1.5%, 2%, and 2.5%) applied to S. aureus and E. coli cultures in vitro using nutrient broth medium. The bacterial populations were quantified after 24 hours of incubation at 37°C, with an initial concentration of 10? CFU/mL. The results indicated that both chitosan and coconut shell liquid smoke exhibited a stronger bactericidal effect against S. aureus than E. coli. The minimum inhibitory concentration of Chitosan against S. aureus was 1%, resulting in a reduction of 2.16 log cycles, whereas the MIC against E. coli was 2%, corresponding to a reduction of 1.47 log cycles. Meanwhile, the minimum inhibitory concentration of coconut shell liquid smoke against S. aureus was 1% (reducing 1.542 log cycles), and against E. coli was 1.5% (reducing 2.02 log cycles). Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and Infrastructure